Diagnostic methods for identifying different Aeromonas species and examining their pathogenicity factors, their correlation to cytotoxicity and adherence to fish mucus. Issue 2 (6th December 2018) - Jung‐Schroers, Verena; Jung, Arne; Ryll, Martin; Bauer, Julia; Teitge, Felix; Steinhagen, Dieter
Abstract: Aeromonas spp. are ubiquitous in the aquatic environment, acting as facultative or obligate pathogens for fish. Identifying Aeromonas spp. is important for pathogenesis and prognosis in diagnostic cases but can be difficult because of their close relationship. Forty‐four already characterized isolates of Aeromonas spp. were analysed by 16S rRNA gene sequencing, by gyrase B sequencing, by analysing their fatty acid profiles, by biochemical reactions and by MALDI‐TOF MS. To determine their pathogenicity, cytotoxicity, adhesion to mucus and the expression of 12 virulence factors were tested. The susceptibility of the isolates towards 13 different antibiotics was determined. MALDI‐TOF MS was found to be an acceptable identification method for Aeromonas spp. Although the method does not detect all species correctly, it is time‐effective and entails relatively low costs and no other methods achieved better results. A high prevalence of virulence‐related gene fragments was detected in almost all examined Aeromonas spp., especially in A. hydrophila and A. salmonicida, and most isolates exhibited a cytotoxic effect. Single isolates of A. hydrophila and A. salmonicida showed multiple resistance to antibiotics. These results might indicate the potentially pathogenic capacity of Aeromonas spp., suggesting a risk for aquatic animals and even humans, given their ubiquitous nature.